2020
DOI: 10.1038/s41523-020-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ductal carcinoma in situ grade via triple-modal molecular imaging of B7-H3 expression

Abstract: Ductal carcinoma in situ (DCIS) will account for 62,930 cases of breast cancer in 2019. DCIS is a pre-invasive lesion which may not progress to invasive carcinoma, yet surgery remains the mainstay treatment. Molecular imaging of a specific marker for DCIS grade for detection and active surveillance are critically needed to reduce potential overtreatment. First, breast cancer marker B7-H3 (CD276) expression was evaluated by immunohistochemical staining in 123 human specimens including benign epithelium (Hscore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Methods that have been studied to improve inter-observer agreement in DCIS grading include evaluating B7-H3 expression [33], using laboratory-and pathologist-specific feedback reports and e-training [34,35] and applying ad hoc dichotomization of histopathologic features to obtain 'ideal' cut-offs for features used in DCIS grading [36]. Although these studies showed promise in reducing grading variation, overall grading variation remained substantial.…”
Section: Introductionmentioning
confidence: 99%
“…Methods that have been studied to improve inter-observer agreement in DCIS grading include evaluating B7-H3 expression [33], using laboratory-and pathologist-specific feedback reports and e-training [34,35] and applying ad hoc dichotomization of histopathologic features to obtain 'ideal' cut-offs for features used in DCIS grading [36]. Although these studies showed promise in reducing grading variation, overall grading variation remained substantial.…”
Section: Introductionmentioning
confidence: 99%
“…Combined photoacoustic and fluorescence molecular imaging of specific cell surface targets using antibodies conjugated to near-infrared dyes is thus a new and promising approach. Previous reports indicated that combined photoacoustic and fluorescent molecular imaging using an anti-B7-H3 antibody-near infrared dye conjugate could differentiate clinically actionable breast carcinoma and ductal carcinoma in situ from normal mammary tissues in a transgenic murine model of breast cancer (17)(18)(19). Hence, it is hypothesized that the highly specific imaging ability of spectroscopic PAMI combined with a preoperatively administered molecularly tumorspecific contrast agent can be leveraged to improve non-invasive identification of occult LN metastasis in HNSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules with high fluorescence QY are good for fluorescence application, whereas NIR dyes with low fluorescence QY can be good candidates for PA contrast agents. Commonly used fluorescence dyes include ICG, 172 , 184 , 185 MB, 186 Evans blue, 187 IRDye800CW, 24 , 188 Alexa Fluor750, 189 , 190 MMPSense 680, 191 NIR caspase-9 probe, 147 800RS 192 etc. Except for ICG, Evans blue, and MB, the other the contrast agents are not FDA-approved for human use; hence, they can be evaluated only in phantoms or animal models.…”
Section: Photoacoustic Imaging With Exogeneous Probesmentioning
confidence: 99%